The use of new communication systems: UTPL brand and digital campaignes [Uso de noevas formas de comunicación: La marca universitaria UTPL y campañas digitales] - Paladines Galarza, F. (2010)
Since internet appeared 40 years ago, it produced a change in communications in general. Education is also involved in this process which includes the use of new technology as a basic tool in the process of information. University, which is in charge of educating human beings, has to understand the evolution of this technology and its applications in education field. Could be useful for people, who works in marketing and communications, to know how to reinforce the communication of an specific brand, using digital campaigns, because Ecuador has 13% of internet users, and they are young people. Besides, this communication systems could lose space.